LEXICAL RELATION ANALYSIS REFERRING TO MUSLIMS ON DONALD TRUMP’S SPEECH; BAN ALL MUSLIMS TRAVEL TO UNITED STATES OF AMERICA - YAQIN, HUSNUL (LANGUAGE HORIZON, 2018)
Abstract This research reviews Donald Trump?s dictions which refer to Muslims in his campaign speech. He keeps arguing that terrorism attacks in America are mostly performed by Muslims which leads to be one of his campaign concerns on banning Muslims travel to America. It becomes issue of debate over the world since the policy program hits sentimental field. Thus, knowing how the tight-loose expression level of them turns to be the interest of this study. The study focuses on semantic relation theory by Riemer and uses qualitative method to reveal the goal. There are various lexical relation terms arise over Donald Trump?s dictions to refer Muslims. They provide variant meanings which can be variation terms to use by speaker. Those terms come over four lexical relations, Antonym, Synonym, Meronym and Hyponym. Donald Trump tended to use tighter meaning words to address Muslims. Hyponymy covers more semantic components than others on componential analysis which indicates looser meaning among others. While in turn, Donald Trump should not use antonymy form to avoid misunderstanding on his audiences. It also indicates tighter meaning since it mostly does not cover any component.